2014
DOI: 10.1103/physrevb.90.014409
|View full text |Cite
|
Sign up to set email alerts
|

Chiral spin liquid in a two-dimensional two-component helical magnet

Abstract: A low-temperature method is developed, suited for the two-dimensional two-component classical helical magnet. Four phases on the phase diagram as functions of temperature and helicity parameter of the Hamiltonian are found. Among the three ordered phases two show magnetic order: the usual algebraic correlations of the magnetization and the algebraic correlations of the magnetization in the frame rotating according with the helical order. A chiral spin liquid phase emerges directly from the paramagnetic phase a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Our calculated critical exponents for the spiral ferromagnet to paramagnet quantum phase transition in the spin orbit coupled spin-1 Bose-Hubbard model (ν ≈ 2/3 and γ ≈ 1/2) point to the possible existence of a new universality class in this problem. Our results for the numerical value of the correlation length exponent are consistent with the universality class of classical uniaxial dipolar ferromangets [65][66][67] and the XY chiral spin liquid transition in two dimensions [68] but the current numerical accuracy of our calculations does not allow us to disentangle this from the possible three-dimensional Ising and XY universality classes. On physical grounds however, it is most natural to expect that our results are consistent with the chiral spin liquid class as this involves a helical magnetic transition.…”
Section: Phase Diagramsupporting
confidence: 51%
See 1 more Smart Citation
“…Our calculated critical exponents for the spiral ferromagnet to paramagnet quantum phase transition in the spin orbit coupled spin-1 Bose-Hubbard model (ν ≈ 2/3 and γ ≈ 1/2) point to the possible existence of a new universality class in this problem. Our results for the numerical value of the correlation length exponent are consistent with the universality class of classical uniaxial dipolar ferromangets [65][66][67] and the XY chiral spin liquid transition in two dimensions [68] but the current numerical accuracy of our calculations does not allow us to disentangle this from the possible three-dimensional Ising and XY universality classes. On physical grounds however, it is most natural to expect that our results are consistent with the chiral spin liquid class as this involves a helical magnetic transition.…”
Section: Phase Diagramsupporting
confidence: 51%
“…It is also possible that we need to compare different channels, as it is non-trivial to compare our estimate of γ to those of the RG since we are computing the order parameter susceptibility from S z (r)S z (r ) , whereas the RG in Ref. [68] computes a "twist" susceptibility, which corresponds to a correlation function quartic in spin operators. At this stage, we are inclined to believe that our system indeed belongs to a new universality class not studied before in the literature, but more work (and possibly more accurate numerical estimates of critical exponents) are necessary before any definitive conclusion can be reached.…”
Section: A Dmrgmentioning
confidence: 99%
“…In our previous study [9], we have not considered the vicinity of the Lifshitz point and have found the simplistic phase diagram ( fig.1d). In the current study, we extend the results and find the diagram (fig.2) consistent with [15,16]. We also investigate the critical properties of topological defects, namely domain walls and vortices.…”
Section: N = 2 K =supporting
confidence: 84%
“…In addition to the reentrant phase transition to the collinear quasi-longrange ordered phase, the authors have found that the anisotropy of the system leads to a non-Ising character of the chiral transition modified by a long-range interaction. In other words, the chiral transition falls to the universality class of the two-dimensional Ising model with strong long-range dipolar interactions [16]. But in our opinion, this conclusion is the consequence of the chosen approximation, when a domain wall along the helix direction is infinitely heavy.…”
Section: N = 2 K =mentioning
confidence: 75%
See 1 more Smart Citation